Efektifitas pendekatan konseling realita dengan teknik WDEP untuk meningkatkan disiplin belajar peserta didik di sekolah menengah kejuruan - Sagita, Bella; Suarni, Ni Ketut; Dharsana, I Ketut (Indonesian Institute for Counseling, Education and Therapy (IICET), 2024)
This study aims to determine the effectiveness of the reality counseling approach with the WDEP technique to improve the learning discipline of class X hospitality students at Singaraja State Vocational School. The method used in this study is experimental. Sampling using random sampling technique. Data collection uses a learning discipline questionnaire. The data analysis technique used parametric statistical analysis, namely by using the Paired-Sample T-Test with the help of the SPSS for window version 20.00 program. This research method aims to determine the effectiveness of the reality counseling approach with the WDEP technique to improve student learning discipline. The design of this study was the Non-Equivalent Control Group Design which was carried out on students in the experimental class and the control class. This study focuses on the changes produced by the reality counseling approach service with the WDEP technique to improve student learning discipline with the data collection technique used, namely a questionnaire. Based on the significance test, it is found that the significance value is 0.000 where 0.000 <0.05, where the Reality Counseling Approach with the WDEP Technique is Effective for Improving Learning Discipline in Class X Hospitality Students at SMK Negeri Singaraja.